Cultural Manifestation in an Electronic EFL Textbook For Senior High School - Imam Santosa (Universitas Bunda Mulia, 2019)
This study aims to find out the manifestation of culture in English electronic textbook for Senior highschool by Puskurbuk. The study utilizes a content analysis as a research method to explore the cultural element in an Electronic English Textbook for Senior high school in Indonesia. The study probes around cultural element or cultural manifestation in the textbook, in which the main points-cultural features in cultural element comprises of eight different manifestations; cultural identity and social group, social interaction, belief and behaviour, social and political institutions, socialization and life cycle, national history, national geography and national identityThe result of this study revealedcultural manifestations in the textbook consisting of 28% stereotype and national identity, which made up to almost one-third of the whole cultural occurrences. The remaining sequential amount of the cultural occurrences in the textbook are cultural identity and social group with 17%. Social and political institution, along with national geography, gained 13% of cultural manifestations. Social interaction (9%), belief and behaviour (7%), socialization and life cycle (7%) and the 6% occurrence of national history were the least elements found in the data observed. This study is beneficial to give the insight of cultural manifestation portrayal in the textbook.Keywords: English Textbook, Culture, Cultural element